Compressive properties and energy absorption of rigid polyurethane foam. Issue 1 (1st November 2022) - Zhang, Zexiong; Zhong, Weizhou; Chen, Junhong; Luo, Jingrun
Abstract : Rigid polyurethane foams (RPUF) are mainly used as a buffer energy absorption material for the protective structure in buildings, ground vehicles, and aircraft. Its mechanical and energy absorption performance is a vital evaluation basis for its use design. Based on uniaxial compression experimental tests, The stress-strain curve of the mechanical behavior of RPUF at different strain rates and temperatures were obtained. The law and mechanism of strain rate and temperature on mechanical behavior and energy absorption are quantitatively analyzed based on experimental results. It was found that the mechanical properties such as yield stress, plateau stress and energy absorption of RPUF at low temperature and high strain rate all have a high improvement, but neither temperature nor strain rate affected the optimal energy absorption state of RPUF. Combined with the experimental results (stress-strain curves of RPUF at different temperatures and strain rates) and the framework of the sheerwood-frost constitutive model, the relevant parameters of the RPUF shape function, strain rate influence term and temperature influence term are obtained. This relationship and parameter can provide accurate material property simulation analysis.